The home literacy environment: Exploring how media and parent–child interactions are associated with children's language production. (December 2014) - Liebeskind, Kara G; Piotrowski, Jessica T; Lapierre, Matthew A; Linebarger, Deborah L
Children who start school with strong language skills initiate a trajectory of academic success, while children with weaker skills are likely to struggle. Research has demonstrated that media and parent–child interactions, both characteristics of the home literacy environment, influence children's language skills. Using a national sample of American parents of children aged 8–36 months ( n  = 500), the current study evaluated how media and parent–child interactions are associated with children's language skills. Results indicated a positive association between literacy-based parent–child interactions and children's language production. The association between access to radios and children's books was mediated by parent–child interactions. These results offer important implications for creating home interventions to boost the language abilities of children before entering school.